2020
DOI: 10.1021/acsami.0c09814
|View full text |Cite
|
Sign up to set email alerts
|

Oral GLP1 Gene Delivery by an Antibody-Guided Nanomaterial to Treat Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is a chronic and progressive hyperglycemic condition. Glucagon-like peptide-1 (GLP1) is an incretin secreted from pancreatic β-cells and helps to produce insulin to balance the blood glucose level without the risk of hypoglycemia. However, the therapeutic application of GLP1 is limited by its intrinsic short half-life and rapid metabolic clearance in the body. To enhance the antidiabetic effect of GLP1, we designed a human cysteine-modified IgG1-Fc antibody-mediated oral gene de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…By examining numerous original research studies on ODDS, we developed a TCA-conjugated CSA (TCSA) nanocarrier as a triple padlock system for oral delivery of recombinant human teriparatide [rhPTH (1–34)] against osteoporosis. In this research, we showed that the TCSA-triple padlock system facilitates protection of encapsulated rhPTH (1–34) from gastric or enzymatic degradation in the GIT and ASBAT- or OST α/β-mediated reabsorption of the TCSA/rhPTH nanocomplex, along with the prolonged t 1/2 , stimulates new bone formation, and reduces osteoporotic fracture by delivering the rhPTH to the type-1 PTH receptor (PTHr-1) through the intestinal portal system.…”
Section: Introductionmentioning
confidence: 99%
“…By examining numerous original research studies on ODDS, we developed a TCA-conjugated CSA (TCSA) nanocarrier as a triple padlock system for oral delivery of recombinant human teriparatide [rhPTH (1–34)] against osteoporosis. In this research, we showed that the TCSA-triple padlock system facilitates protection of encapsulated rhPTH (1–34) from gastric or enzymatic degradation in the GIT and ASBAT- or OST α/β-mediated reabsorption of the TCSA/rhPTH nanocomplex, along with the prolonged t 1/2 , stimulates new bone formation, and reduces osteoporotic fracture by delivering the rhPTH to the type-1 PTH receptor (PTHr-1) through the intestinal portal system.…”
Section: Introductionmentioning
confidence: 99%
“…Special considerations should be given to developing successful antiadhesion agents that are highly effective and safe in preventing adhesion, easy to use, and cost-effective in routine surgery . Biocompatible polymers are nontoxic , and vastly used to apply physical barriers directly to the body. ,, However, only biocompatible polymers without any other supporting material cannot be applied successfully to the patients because of the gravitational pull that flows down from the damaged tissue surface . Increasing the injected amount of antiadhesion agent does not allow the use of large amounts of antiadhesion agent because of the psychological burden and concerns of abuse caused by excessive administration in the body .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Special considerations should be given to developing successful antiadhesion agents that are highly effective and safe in preventing adhesion, easy to use, and cost-effective in routine surgery. 15 Biocompatible polymers are nontoxic 16,17 T h i s c o n t e n t i s and vastly used to apply physical barriers directly to the body. 9,18,19 However, only biocompatible polymers without any other supporting material cannot be applied successfully to the patients because of the gravitational pull that flows down from the damaged tissue surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, it took approximately 14 days for the second-generation containing 500 μg of GLP1 per dose to reach the target glycemic level in the Lepr DB /Lepr DB mice after multiple administrations. 4 The number and amount of doses, poor transfection efficiencies, and slow therapeutic outcomes of previous oral dosage forms have led us to develop an optimized and effective oral dosage form targeting T2DM.…”
mentioning
confidence: 99%
“…It was only effective for pre-T2DM mice model (DIO) but not for the Lepr DB /Lepr DB and Lepr OB /Lepr OB mouse models that are well-accepted diabetes animal models recapitulating human T2DM characterized by the progressive development of high blood glucose level, insulin resistance, and β cell loss. However, it took approximately 14 days for the second-generation containing 500 μg of GLP1 per dose to reach the target glycemic level in the Lepr DB /Lepr DB mice after multiple administrations . The number and amount of doses, poor transfection efficiencies, and slow therapeutic outcomes of previous oral dosage forms have led us to develop an optimized and effective oral dosage form targeting T2DM.…”
mentioning
confidence: 99%